The reflection of partnership context on implementation and process outcomes in cross-sector social partnerships : the case of a local red cross in Portugal - Carrilho, Tiago (2014)
In this article the research question is the following: how partnership context inherent to target-group problems and organizational flexibility of origin institutions is reflected on the implementation and process outcomes of partnerships? We studied three interventions directed towards active ageing and employment promotion on the unemployed with low qualifications, which integrated non-profit institutions, local public institutions, SME and an enterprise association. The local Red Cross was the convener. Based on case study methodology we analyzed sixteen semi-directed interviews of partners’ representatives and the documentation of each intervention. The complex nature of the problems had implications on the implementation in terms of the diverse resources and partners involved, the collaborative and organizational levels of intervention, and in feed-backs based upon joint continuous evaluation of the actions directed towards target-groups. The flexibility of origin institutions had implications on the implementation in terms of the decision autonomy of the representatives, involvement of other members of the origin institutions in the intervention, financial and human resources limitations of partner-institution, and strategic SME integration of the social values of the non-profit institutions. The interventions which focused on feminine self-employment and active ageing co-created value due to the reformulation of goals and actions, increased partner skills for mutual benefit and increased interdependence awareness. The SME involved in the feminine self-employment intervention developed new organizational skills and social responsibility evaluation.